1966
DOI: 10.1099/00221287-42-1-133
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cellular Lipid in the Resistance of Gram-positive Bacteria to Penicillins

Abstract: SUMMARYIt has been shown that when the Gram-positive micro-organisms Bacillus subtilis, Staphylococcus aureus and Streptococcus faecalis were grown under conditions in which their cellular lipid was increased a corresponding increase in their resistance to the penicillins benzylpenicillin, cloxacillin, methicillin and quinacillin was produced. Likewise cell-wall lipid depletion caused a corresponding increase in sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1967
1967
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The composition of bacterial lipids and their structural arrangement might prevent the entrance or binding of different antibacterial agents (1). Changes in lipid composition have been found after mutation to drug resistance in various species (7,11,15,29). Except for an increase in the amount of palmitic acid, no significant differences in sugars of fatty acids were found when crude LPS preparations from strains D21 and D22 were compared ( Table 3), indicating that at least the carbohydrate part of LPS is not the target of the envA mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of bacterial lipids and their structural arrangement might prevent the entrance or binding of different antibacterial agents (1). Changes in lipid composition have been found after mutation to drug resistance in various species (7,11,15,29). Except for an increase in the amount of palmitic acid, no significant differences in sugars of fatty acids were found when crude LPS preparations from strains D21 and D22 were compared ( Table 3), indicating that at least the carbohydrate part of LPS is not the target of the envA mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have suggested that there may be a relation between antibiotic resistance and the lipid content of bacterial cells (4,8,9). Dunnick and O'Leary (4) reported that an antibioticresistant strain of S. aureus contained more lipid than a susceptible strain.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in total lipid or fatty acid composition, or both, have been associated with an increased antibiotic resistance in various bacteria, and it has been suggested that the lipid composition may be of importance in preventing the entrance or binding of the antibiotic to the cell (2,9,11,(13)(14)(15). However, the divergence of results obtained does not allow any general conclusions to be drawn with regard to the role of lipids in the development of resistance.…”
mentioning
confidence: 42%